1995
DOI: 10.1021/ie00041a015
|View full text |Cite
|
Sign up to set email alerts
|

Optimization and Control of Semibatch Reactors

Abstract: We propose an integrated method for optimization and control of semibatch reactors. Based on the desired control objective, dynamic programming is applied to obtain optimal operating trajectories. Yield optimization is assured for a real plant by tracking model-dependent optimal trajectories according to the proposed modified globally linearizing control (MGLC) structure. The behavior of the proposed MGLC structure is predictable and reliable, with tuning parameters based on the proposed tuning method if the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Examples arise in the scheduling of batch processes, the dynamic optimization of batch reactors, and the determination and tracking of process start-up and shut-down trajectories (Terwiesch et al, 1994;Chang and Hseih, 1995). …”
Section: Introductionmentioning
confidence: 99%
“…Examples arise in the scheduling of batch processes, the dynamic optimization of batch reactors, and the determination and tracking of process start-up and shut-down trajectories (Terwiesch et al, 1994;Chang and Hseih, 1995). …”
Section: Introductionmentioning
confidence: 99%
“…In order to illustrate the usefulness of the proposed approach to a multi-input multi-output (MIMO) system, a semi-batch reactor, where hexyl monoester of maleic acid is formed by the reaction of hexanol with maleic anhydride, is considered [1] (details included in Appendix A). The input variables that can be used for manipulation are the reactant flow rate, U 1 , and the coolant flow parameter, U 2 .…”
Section: Simulation Studiesmentioning
confidence: 99%
“…For this system, the optimal control problem formulation, together with the constraints, is reported in Appendix A. For the production of hexyl ester of maleic acid in a semi-batch reactor, Chang and Hsieh [1] have reported that it is possible to achieve 99% conversion in 8000 s by adopting a constant rate of reagent and full cooling policy, whereas minimum time required to achieve this target is 6570 s. Therefore, in this study, we consider the final time to be fixed at 6570 s, and the data generation for modeling this system has also been carried out considering a single fixed final time of 6570 s.…”
Section: Simulation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…During that time many different concepts of semi-batch reactor control were developed. The most promising of these were the concepts of adaptive control [3,18], optimal control [2,8,19] and especially modelpredictive control schemes, which are the most frequently used [4,5,9,[11][12][13]16,17]. Model predictive control was very successful in solving many industrial control problems [1,6,7].…”
Section: Introductionmentioning
confidence: 99%